Two-colour Three-pulse Spectrally Resolved Nonlinear Spectroscopy for Studies of Dynamics in Semiconductor Si Quantum Dots - Cuong, Vuong Van; Khuong, Dinh Ba; Lap, Dao Van (Communications in Physics, 2020)
We demonstrate that a two-colour three-pulsenonlinear spectroscopy can be used to study the dynamics of excited carriers inSi quantum dot structures embedded in SiN. Decays of the transverse optical phonon population and the transverse acoustic phonon population are measured and discussed. A simple theoretical modelis also used to support interpretation of our experimental observations.